Impact on percutaneous coronary intervention for acute coronary syndromes during the COVID-19 outbreak in a non-overwhelmed European healthcare system: COVID-19 ACS-PCI experience in Ireland. Issue 4 (2nd April 2021) - Connolly, Niall Patrick; Simpkin, Andrew; Mylotte, Darren; Crowley, James; O'Connor, Stephen; AlHarbi, Khalid; Kiernan, Thomas; Arockiam, Sacchin; Owens, Patrick; John, Amal; Blake, Gavin J; Fitzgerald, Sean; et al.
Abstract : Aims: To evaluate temporal trends of acute coronary syndromes (ACS) treated via percutaneous coronary intervention (PCI) throughout the COVID-19 outbreak in a European healthcare system affected but not overwhelmed by COVID-19-related pathology. Methods and results: We performed a retrospective multicentre analysis of the rates of PCI for the treatment of ACS within the period 2 months pre and post the first confirmed COVID-19 case in Ireland, as well as comparing PCI for ST-elevation myocardial infarction (STEMI) with the corresponding period in 2019. During the 2020 COVID-19 period (29 February–30 April 2020), there was a 24% decline in PCI for overall ACS (incidence rate ratio (IRR) 0.76; 95% CI 0.65 to 0.88; p<0.001), including a 29% reduction in PCI for non-ST-elevation ACS (IRR 0.71; 95% CI 0.57 to 0.88; p=0.002) and an 18% reduction in PCI for STEMI (IRR 0.82; 95% CI 0.67 to 1.01; p=0.061), as compared with the 2020 pre-COVID-19 period (1 January–28 February 2020). A 22% (IRR 0.78; 95% CI 0.65 to 0.93; p=0.005) reduction of PCI for STEMI was seen as compared with the 2019 reference period. Conclusion: This study demonstrates a significant reduction in PCI procedures for the treatment of ACS since the COVID-19 outbreak in Ireland. The reasons for this decline are still unclear but patients need to be encouraged to seek medical attention when cardiac symptoms appear, in order to avoid incremental cardiac morbidity and mortality due to a reduction in coronary revascularisation for the treatment of ACS.